Exploration of the Brn4‐regulated genes enhancing adult hippocampal neurogenesis by RNA sequencing. Issue 10 (18th February 2017) - Guo, Jingjing; Cheng, Xiang; Zhang, Lei; Wang, Linmei; Mao, Yongxin; Tian, Guixiang; Xu, Wenhao; Wu, Yuhao; Ma, Zhi; Qin, Jianbing; Tian, Meiling; Jin, Guohua; et al.
Abstract : Adult hippocampal neurogenesis is essential for learning and memory, and its dysfunction is involved in neurodegenerative diseases. However, the molecular mechanisms underlying adult hippocampal neurogenesis are still largely unknown. Our previous studies indicated that the transcription factor Brn4 was upregulated and promoted neuronal differentiation of neural stem cells (NSCs) in the surgically denervated hippocampus in rats. In this study, we use high‐throughput RNA sequencing to explore the molecular mechanisms underlying the enhancement of adult hippocampal neurogenesis induced by lentivirus‐mediated Brn4 overexpression in vivo. After 10 days of the lentivirus injection, we found that the expression levels of genes related to neuronal development and maturation were significantly increased and the expression levels of genes related to NSC maintenance were significantly decreased, indicating enhanced neurogenesis in the hippocampus after Brn4 overexpression. Through RNA sequencing, we found that 658 genes were differentially expressed in the Brn4‐overexpressed hippocampi compared with GFP‐overexpressed controls. Many of these differentially expressed genes are involved in NSC division and differentiation. By using quantitative real‐time PCR, we validated the expression changes of three genes, including Ctbp2, Notch2, and Gli1, all of which are reported to play key roles in neuronal differentiation of NSCs. Importantly, the expression levels of Ctbp2 and Notch2 were also significantly changed in the hippocampus of Brn4 KO mice, which indicates that the expression levels of Ctbp2 and Notch2 may be directly regulated by Brn4. Our current study provides a solid foundation for further investigation and identifies Ctbp2 and Notch2 as possible downstream targets of Brn4. © 2017 Wiley Periodicals, Inc. Abstract : Our previous studies indicated that Brn4 was upregulated and promoted neuronal differentiation of neural stem cells (NSCs) in the surgically denervated hippocampus in rats. In this study, we used high‐throughput RNA sequencing to explore the molecular mechanisms underlying the enhancement of adult hippocampal neurogenesis induced by lentivirus‐mediated Brn4 overexpression in vivo. RNA sequencing revealed that 658 genes were differentially expressed in the Brn4‐overexpressed hippocampi compared with GFP‐overexpressed controls and that the expression levels of genes related to neuronal development and maturation were significantly increased and the expression levels of genes related to NSC maintenance were significantly decreased, indicating enhanced neurogenesis in the hippocampus after Brn4 overexpression. Real‐time PCR validated the expression changes of Ctbp2, Notch2, and Gli1. Importantly, the expression levels of Ctbp2 and Notch2 were also significantly changed in the hippocampus of Brn4 KO mice, which indicates that the expression levels of Ctbp2 and Notch2 may be directly regulated by Brn4. Our current study provides a solid foundation for further investigations and identifies Ctbp2 and Notch2 as possible downstream targets of Brn4.